Quality of service enabled resource scheduling for cooperative driving provision in the internet of vehicles. (15th July 2022) - Ahmad, Iftikhar; Kalsoom, Nafeesa; Khalid, Samina; Ahmed, Zaheed
Road traffic efficiency may be improved by developing an integrated network for cooperative driving provision (CDP) among vehicles on the road. In a dance urban traffic scenario, the quality of service may be compromised when required bandwidth is not provided by the existing network architecture that impacts negatively on the cooperative behaviour of the vehicles. To solve these problems, a network architecture with better scheduling of resources that meet the quality of service (QoS) is required. So, we proposed a fifth-generation (5G) technology-based network architecture that provides the required QoS for CDP. The proposed architecture consists of a resource scheduling mechanism within the 5G network and a scheme for cooperative behaviour among the vehicles on the road. The implementation of the proposed network architecture is done by incorporating it into a well-known vehicular clustering algorithm. The performance of the proposed architecture is compared with existing schemes that show improvement.